Pengaruh Kepemimpinan Kepala Sekolah dan Kinerja Guru terhadap Pendidikan Berkarakter Religius bagi Peserta Didik di SMP PAB 10 Medan Estate - Aldi Bayu Anggara; Muhammad Rifa’i; T. Darmansah (Lembaga Pengembangan Kinerja Dosen, 2025)
The leadership of the school principal and the performance of teachers greatly influence the religious character of education for students. This research aims to describe (1) to determine and analyze the influence of school principal leadership on education with a religious character (2) to determine and analyze the influence of teacher performance on education with a religious character (3) to determine and analyze the influence of principal leadership and teacher performance on education religious character. This research uses quantitative methodology. The population used in this research were students at PAB 10 Medan Estate Middle School. The sample in this research was 50 respondents. Data collection was carried out using a questionnaire. There are 3 research variables, namely: school principal leadership (X1), teacher performance (X2), and religious character (Y). Data analysis used in this research is multiple linear regression, F test, T test, coefficient of determination test (R2), heteroscedasticity test, multicollinearity test. The results of the research conducted show that the principal's leadership and teacher performance together have a significant effect on religious character. This can be seen from the results This can be seen from the results of the F test, namely that the Fcount value is 19.936. The conclusion is that Fcount > Ftable (19.936 > 3.20) meaning that the leadership of the principal X1 and the performance of teacher X2 simultaneously influence religious character (Y).